Transfobia estrutural no cárcere brasileiro: uma análise da ineficácia normativa e do comportamento jurisdicional - Ferreira, Pedro (2022)
Prison, in general, is recognized for being an environment in which inhumane treatment of prisoners is common. In the case of transgender women and transvestites, there is an aggravating factor, since, in addition to experiencing this context of dehumanization like any other person in custody, they are victims of transphobia. In view of this transphobic scenario, in recent years normative acts have been published on the treatment of LGBT+ people deprived of their liberty and, moreover, the Federal Supreme Court has started to discuss the allocation of transgender women and transvestites in Brazilian prison. Given this situation, the present research aims to analyze how the penal system deals with transgender women and transvestites, especially those deprived of their liberty, so that it is possible to verify whether the origin of ADPF n° 527 and Resolution n° 348/ 20, of the CNJ, are able to stop transphobic violence in the prison system. For this, at first, the work seeks to explore the cisgender and heteronormative historical context to understand the process of imposing the deviant status on transgender women and transvestites, as well as its reflexes in the penal and criminological system. Then, it investigates how transgender women and transvestites are currently criminalized, as well as the way they are treated in male prisons. Finally, normative provisions related to the incarceration of transgender women and transvestites are analyzed, in particular Resolution n° 348/20, of the CNJ, and the possible effects of ADPF n° 527. In order to carry out this study, official and unofficial public documents are explored and three theories are adopted as theoretical-methodological references: queer, the criminology of social reaction and queer criminology. These theories helped in the construction of the hypothesis that transphobia is a structural problem in the prison system, which makes it impossible for Resolution n° 348/20, of the CNJ, and the origin of ADPF n° 527 is suficiente to stop transfobia in brazilian prision.